Development of Scratch-Based POEDU Digital Media Incorporating Children’s Songs to Improve Fifth-Grade Students’ Poetry Reading Skills - Novanda, Shabilla; Sutikno, Putri Yanuarita (Jurnal Paedagogy, 2026)
This study aims to develop a digital learning medium called POEDU (Poetry Education), assisted by children’s songs and developed using Scratch, and to examine its feasibility and effectiveness in improving fifth-grade students’ poetry reading skills at SDN 3 Kedu. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research subjects were 21 fifth-grade students, with a small-group trial involving 6 students and a large-group trial involving all 21 students. Data were collected through interviews, observations, expert validation questionnaires, and pretest–posttest assessments. Data analysis was conducted using descriptive qualitative and quantitative approaches, supported by the Shapiro–Wilk normality test, paired-samples t-test, and N-Gain analysis to evaluate the effectiveness of the developed media. The results showed that the POEDU media obtained an average expert validation score of 93.33%, indicating a highly feasible category. The paired-samples t-test results revealed a significance value of p < 0.05, demonstrating a significant improvement in students’ poetry reading skills after using the media. Furthermore, the N-Gain scores were 0.5518 for the small-group trial and 0.4527 for the large-group trial, both categorized as moderate. In conclusion, Scratch-based POEDU digital media assisted by children’s songs is highly feasible and effective for improving elementary school students’ poetry reading skills. This study highlights the potential of technology integration in supporting innovative, interactive, and meaningful learning experiences in primary education.